In vitro Cytotoxic Activity of Some Fecal Filtrates - Khdir, Karokh Ali; Al-Jaff, Bahrouz Mahmood (Sulaimani Journal for Pure and Applied Sciences, 2020)
Animal feces have been studied and recognized as a crucial resource for exploring and discovering new novel bioactive compounds produced by host, microbiota, or host- microbiota interaction that may have therapeutic importance. To investigate the cytotoxic effect of human (healthy and colorectal cancer), dog, and cow fecal filtrates that serves as natural bioreactors. The cytotoxic activity was calculated as inhibitory concentration (IC50) based on the percentage of % viability using MTT 3-(4, 5-dimethythiazol-2-yl)-2, 5-diphenyl tetrazolium bromide) assay for 4 crude cell-free fecal filtrates and their Sephadex G100 fractions in vitro against HeLa human cervical cancer cell line. The optical densities (OD) of the fractions were checked at wavelength of 280 nm and considered in the assay rather than cytotoxic active compound concentrations. Cytotoxic activity of each crude fecal filtrate appeared to be dose-dependent (P<0.001) and less active than 40-400 μg/ml 5-flourouracil (5-FU). IC50 for dog, cow, healthy human, colorectal fecal filtrates, and 5-FU were 442.64 ± 23.29, 1265 ± 35.8, 1715 ± 56.9, 400.76 ± 32 and 134.33 ± 3.29 μg/ml respectively. Out of 11 dog fecal filtrate fractions, 4 fractions (F4, F5, F6 and F7) were within IC50 range. Out of 10 cow fecal filtrate fractions, 3 fractions (F3, F5 and F6) were within IC50 range. Out of 11 healthy human fecal filtrate fractions, 2 fractions (F3 and F4) were within IC50 range. Out of 12 colorectal fecal filtrate fractions; 4 fractions (F2, F3, F4 and F6) were within IC50 range against HeLa cells. The crude fecal filtrates and their fractions were with apparent cytotoxic activity showed that the colorectal patients and dogs’ fecal filtrates have higher cytotoxic activity followed by cows and then the healthy humans. This step could be a start for identifying compounds responsible for cytotoxic activity in hope to explore new medicine with therapeutic activity against cancer.
Keywords: Fecal filtrate; Mixed fermentation; Cytotoxic activity; Cervical cancer cells